2014
DOI: 10.5194/acp-14-7883-2014
|View full text |Cite
|
Sign up to set email alerts
|

Acidic reaction products of monoterpenes and sesquiterpenes in atmospheric fine particles in a boreal forest

Abstract: Abstract. Biogenic acids were measured in aerosols at the SMEAR II (Station for Measuring Forest EcosystemAtmosphere Relations II) station in Finland from June 2010 until October 2011. The analysed organic acids were pinic, pinonic, caric, limonic and caryophyllinic acids from oxidation of α-pinene, β-pinene, limonene, 3 -carene and β-caryophyllene, respectively. Due to a lack of authentic standards, the caric, limonic and caryophyllinic acids were synthesised for this study. The mean, median, maximum and mini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 42 publications
(48 reference statements)
5
24
1
1
Order By: Relevance
“…Among the pinene derived oxidation products, MBTCA (3-methyl-1,2,3-butanetricarboxylic acid) was observed to be the most abundant individual monoterpene oxidation product, with concentrations of up to 73 ng m −3 , followed by pinonic acid with a maximum concentration of 46 ng m −3 (van Eijck, 2013). Interestingly, these concentrations are in the same range as monoterpene oxidation products measured during summertime in boreal forest environments (Vestenius et al, 2014), ecosystems which are known to strongly emit monoterpenes. However, these observations of high monoter- pene product concentrations match with the high monoterpene mixing ratios measured at the same site (Yáñez-Serrano et al, 2015).…”
Section: Chemical Composition Of Secondary Organic Aerosolsupporting
confidence: 54%
See 1 more Smart Citation
“…Among the pinene derived oxidation products, MBTCA (3-methyl-1,2,3-butanetricarboxylic acid) was observed to be the most abundant individual monoterpene oxidation product, with concentrations of up to 73 ng m −3 , followed by pinonic acid with a maximum concentration of 46 ng m −3 (van Eijck, 2013). Interestingly, these concentrations are in the same range as monoterpene oxidation products measured during summertime in boreal forest environments (Vestenius et al, 2014), ecosystems which are known to strongly emit monoterpenes. However, these observations of high monoter- pene product concentrations match with the high monoterpene mixing ratios measured at the same site (Yáñez-Serrano et al, 2015).…”
Section: Chemical Composition Of Secondary Organic Aerosolsupporting
confidence: 54%
“…Very few measurements exist of sesquiterpene oxidation product concentra- tions and actually none in tropical forests, which complicates a comparison. Measurements in boreal ecosystems (Vestenius et al, 2014) showed mean summertime concentrations of caryophyllinic acid (one of the β-caryophyllene oxidation products) of about 8 ng m −3 , which is a high concentration for a single compound compared to the concentrations measured at ATTO, where the measured concentration range of caryophyllinic acid is 0.26-1.38 ng m −3 . In summary, the contribution of monoterpene oxidation products to SOA at ATTO is relatively high and essentially comparable with their contribution to boreal forest SOA, whereas the contribution of sesquiterpene products is much less (about 1/10) than in boreal forest ecosystems.…”
Section: Chemical Composition Of Secondary Organic Aerosolmentioning
confidence: 99%
“…Table 1 gives relevant molecular parameters and gas-phase mixing ratios. The gas-phase mixing ratios are assumed to be constant over time (steady state) as might be achieved in a flow reactor, and the values chosen are typical of what might be observed during NPF in a boreal forest (Vestenius et al, 2014). Molecular volatility is expressed in terms of the saturation concentration, C * , which is the equilibrium vapor pressure in units of µg m −3 (Donahue et al, 2006).…”
Section: Model Descriptionmentioning
confidence: 99%
“…In the growing season, forested boreal regions emit biogenic volatile organic compounds (BVOCs) (isoprene, terpenes and sesquiterpenes) into the atmosphere (Kourtchev et al, 2005;Ehn et al, 2012;Noe et al, 2012;Ebben et al, 2011;Vestenius et al, 2014), and their oxidation products contribute to SOA formation or condense onto already 14382 E. F. Mikhailov et al: Long-term measurements (2010-2014 formed particles during transport, increasing aerosol sizes and mass (Tunved et al, 2006;Hallquist et al, 2009;Liao et al, 2014). Since the emission of the organic particle precursors depends on air temperature (Isidorov et al, 1985;Lappalainen et al, 2009), the SOA mass concentration also positively correlates with temperature (Leaitch et al, 2011;Corrigan et al, 2013;Liao et al, 2014).…”
Section: Near-pristine Airmentioning
confidence: 99%